PEMBERIAN ABU SEKAM PADI DENGAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) PADA TANAH GAMBUT - Hary Suranto; Jurnawaty Sjofjan; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to study the giving effect of rice husk ash with good NPK fertilizer towards the growth and production of sweet corn in peat soil. This experiment was conducted at the experimental farm of the Agriculture Faculty, Rimbo Panjang, Kampar and carried out in Juni until September 2014. This research was carried out experimentally using randomized block design (RBD) non factorial consisted of 6 treatments with 4 repetitions which resulting 24 experimental plots. Each experimental unit consisted of 24 plants and 6 plants as samples. The treatments were: AN1: without rice husk ash with NPK 300 kg/ha (135 g/plot), AN2: rice husk ash 3 ton/ha (1350 g/plot) with NPK 300 kg/ha (135 g/plot), AN3: rice husk ash 6 ton/ha (2700 g/plot) with NPK 300 kg/ha (135 g/plot), AN4: without rice husk ash with NPK 600 kg/ha (270 g/plot), AN5: rice husk ash 3 ton/ha (1350 g/plot) with NPK 600 kg/ha (270 g/plot), AN6: rice husk ash 6 ton/ha (2700 g/plot) with NPK 600 kg/ha (270 g/plot). The results of experiment that was obtained using analysis of variance were tested further with DNMRT (Duncan's New Multiple Range Test) at the level 5%. Based on the results of this research, the recommended doses are rice husk ash 3 ton/ha (1350 g/plot) and NPK 600 kg/ha (270 g/plot). Keywords: sweet corn, rice husk ash, NPK fertilizer